Characteristics of Silica Sand from Alvarado, Veracruz, Mexico as material for Permeable Reactive Barriers for the Remediation of Aquifers contaminated with leachates from uncontrolled landfills - Susunaga Miranda, Manuel Alberto; Estévez-Garrido , Bertha María; Susunaga-Estévez , Rodrigo Manuel (Enfoque UTE, 2020)
This article characterizes the silica sand from the coasts of the municipality of Alvarado, Veracruz, Mexico and compares its properties with the materials used for the Permeable Reactive Barriers and that allow its use as a solution for the remediation of aquifers contaminated with leachate from uncontrolled landfills, by granulometric analysis, determination of humidity and concentration of Silica and Iron, obtaining particles with a diameter of 0.707 mm, relative humidity of 0.52% and concentration of SiO2 and Fe2O3 87.38% and 2.72% respectively, which comparing with reactive materials in use meets the criteria to be used as a Barrier for the Remediation of Aquifers contaminated with leachates.